Art at the turn of the Rue de Seine et la Rue de l'Échaudé. - Gangitano, Lia; Hiddelston, Anna (Paris : Galerie Loevenbruck, 2002)
Opened at the beginning of 2001, with Bruno Peinado's one-man exhibition the Galerie Loevenbruck sees its vocation as promoting, supporting and bringing contemporary art and the artists who take part in its evolution to public attention. The approach to this field of creative work is deliberately historical. The various objects aim at supporting artists who force breaches in different fields of contemporary art. The object of this book is to make the range of work done by the artists with whom we have been fortunate to work during these first two years known to a wider audience.
per kunstenaar biog., bibliog.
Duits & Engels & Frans
boek
Keywords: Barré, Virginie; Blanckart, Olivier; Declercq, Alain; Königsfeld, Dirk; Labaume, Vincent; Labelle-Rojoux, Arnaud; Laurent, Rachel; Mayaux, Philippe; Peinado, Bruno; Saethre, Borre; Sautour, Stéphane